Hydrogen bonding and rate enhancement in the photoinduced polymerization of telechelic urethane methacrylates based on a cycloaliphatic system: tricyclodecane dimethanol - Deepak, V. D.; Rajan, J.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
A new class of telechelic urethane methacrylic crosslinkers, based on a cycloaliphatic system (tricyclodecane dimethanol and tricyclodecane monomethanol), was synthesized. The synthesis was achieved by a two-step condensation of 1,6-hexamethylene diisocyanate or isophorone diisocyanate with tricyclodecane dimethanol and capping with hydroxyethyl methacrylate. Samples of hexanediol diacrylate, tricyclodecane monomethacrylate, and tricyclodecane dimethacrylate were used as non-hydrogen-bonding monomers for comparative studies of the curing kinetics. The photopolymerization of these telechelic systems was investigated with UV irradiation in the presence of 2,2-diethoxy acetophenone as the photoinitiator, and the kinetics were followed by the monitoring of the double-bond conversion at 815 cm−1 with Fourier transform infrared spectroscopy. The hydrogen-bonded crosslinkers had higher double-bond conversions than their non-hydrogen-bonded counterparts under identical conditions. The higher cure rate could be explained by hydrogen-bonding preassociation in these systems, which brought the methacrylate double bonds within close proximity. The temperature effects on the hydrogen bonding were also investigated. A decrease in the extent of the double-bond conversion with increasing temperature was observed for the hydrogen-bonded crosslinker, in contrast to an increased conversion with temperature for hexanediol diacrylate and tricyclodecane dimethacrylate. This was directly indicative of a reduction of hydrogen bonding at elevated temperatures leading to lower conversions. © 2006 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 44: 4384–4395, 2006

Self-organization-induced three-dimensional honeycomb pattern in structure-controlled bulky methacrylate polymers: - Deepak, V. D.; Asha, S. K. (Journal of Physical Chemistry B, 2006)
Here we report, for the first time, a novel molecular design for three-dimensional honeycomb structures through a self-organization of hydrogen-bonded bulky anchoring group in a methacrylic polymer backbone. The polymerizable monomer design includes a methacrylic double bond linked to various hydrophobic anchoring units such as ethane, n-decane, tricyclodecane (TCD), and adamantane via a hydrogen-bonded cycloaliphatic urethane linkage. The structures of the polymers were confirmed by nuclear magnetic resonance (NMR) and the molecular weights of the polymer were determined by gel permeation chromatography (GPC). The methacrylate polymers having tricyclodecane and adamantane bulky anchoring groups self-organized to produce three-dimensional honeycomb patterns in tetrahydrofuran−water solvent mixture at ambient conditions, whereas its linear analogues (ethane, n-decane) failed to produce any micropattern. The scanning electron microscopy (SEM) analysis of the above-prepared polymer films revealed that the structure of the polymer played a major role in the formation of the honeycomb patterns. The solution Fourier transform infrared (FTIR) measurements confirmed that the bulky tricyclodecane and adamantane polymers have strong hydrogen-bonding interaction compared to that of their linear analogues, which is the driving force for the micropatterns. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) analysis of the bulky polymers revealed that the polymers exist as vesicles or micelles in the solution, which leads to the formation of the honeycomb pattern. The honeycomb pattern formation in the bulky polymer systems suggests that two cooperative factors such as hydrogen-bonding interaction and hydrophobicity of bulky anchoring units are necessary to induce three-dimensional honeycomb structures. To investigate the effect of molecular weights and its distribution on the self-organization process, both benzoyl peroxide (BPO) initiated free radical and atom transfer radical polymerization (ATRP) techniques were employed for the polymerization. Micropores formed irrespective of differences in molecular weight and polydispersity index (PDI); however, the pore size distribution was influenced by both molecular weights and PDI. Low molecular weight samples afforded polydisperse pores with the ATRP samples with more narrow PDI producing pores with large dimensions. The approach has also been investigated for polystyrene-bulky methacrylic copolymer, and the results revealed that uniform honeycomb patterns were produced for copolymers having more than 50 mol % incorporation of bulky units.

Random and AB diblock copolymers of tricyclodecanemethanol urethane methacrylate with styrene: synthesis and morphology characterization - Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A: Polymer Chemistry, 2008)
A monomer design having a bulky terminal tricyclodecane (TCD) unit linked via hydrogen bondable urethane to an ethyleneoxy methacrylate unit, and capable of generating three-dimensional honeycomb patterns upon solvent casting has been investigated. Random copolymers as well as a diblock copolymer Poly(Sty42-b-TCD18) of this monomer with styrene were prepared by free-radical polymerization route and atom transfer radical polymerization (ATRP) route. Morphology characterization was carried out using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis. Particle size was measured by dynamic light scattering measurements (DLS). Irrespective of the wide differences in molecular weight and polydispersity index values, the random copolymers having TCD content >30 mol % were found to form microporous films upon solvent casting from a THF/water 9:1 solvent combination. The amount of TCD in the copolymer was found to have an influence on the pore size formed. The diblock copolymer formed microspheres ∼200 nm in diameter. The thermal properties of all the polymers were studied using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), and the copolymers were found to have good thermal stability. © 2008 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 46: 1278–1288, 2008

Photophysical investigation into the self-organization in pyrene-based urethane methacrylate comb polymer - Deepak, V. D.; Asha, S. K. (Journal of Physical Chemistry B, 2009)
A side chain urethane methacrylate polymer with pendant pyrene units was synthesized and investigated for its self-organizing process in solution by UV-vis and fluorescence spectra and in film by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and fluorescence microscopy. The polymer exhibited excimer emission centered at 476 nm, even at very dilute concentrations (10(-6) M) as a consequence of the polymer design with pendant pyrene units on every side chain. A change in aggregation pattern was observed upon increasing the concentration to 10(-4) M. New red-shifted peaks appeared in the UV-vis absorption spectra and the I(E)/I(M) ratio, and the peak I/peak III ratio showed a break around 10(-4) M, suggesting formation of stable ground state aggregates. This was further confirmed by the SEM, TEM, AFM and fluorescence microscope studies, which showed the formation of vesicles in THF and giant spherical aggregates in THF/H(2)O. The change in pattern of aggregate formation with concentration also coincided with a sudden increase in the intensity of the hydrogen bonded urethane N-H peak with concentration as recorded by solution FT-IR studies in THF.

Correlation of architecture with excimer emission in 100% pyrene-labeled self-assembled polymers - Kaushlendra, K.; Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2011)
Pyrene was incorporated as pendant unit to side-chain urethane methacrylate polymers having a short ethyleneoxy or a long polyethyleneoxy spacer segment. The short-spacer pyrene urethane methacrylate was also incorporated either as block or random copolymer (1:9) along with polystyrene. The excimer emission was observed to be different for different polymers with the random copolymer exhibiting the lowest efficiency. But, the total quantum yield was highest (phi = 0.58) for random copolymer due to the high emission coefficient of monomer compared to that of excimer. The polymer dynamics were compared by steady state emission and fluorescence decay in THF or THF/water (9:1) solvent mixture and films. The solid state decay profile showed decay without a rise time indicating presence of ground state aggregates. In THF/water (9:1), the decay profile at the excimer emission (500 nm) showed a rise time indicating dynamic excimers. The evolution of excimeric emission centred similar to 430 or similar to 480 nm as a function of temperature was also studied in THF/water (9:1). The I(E)/I(M) ratio for the lambda(343) nm excitation exhibited steady increase with temperature with the block copolymer PS-b-PIHP exhibiting the highest ratio and highest rate of increase; whereas, the random copolymer PS-r-PIHP had the lowest I(E)/I(M) ratios. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1678-1690, 2011
Keywords: I(E)/I(M) ratio; Morphology; pyrene; Self-assembly; structure-property relations; time-resolved and variable temperature fluorescence